ANALISIS SEMANTIK PUISI “AKU” KARYA CHAIRIL ANWAR - Meinanda, Cicha; Arsanti, Meilan (Jurnal Akselerasi Merdeka Belajar dalam Pengabdian Orientasi Masyarakat (AMPOEN): Jurnal Pengabdian kepada Masyarakat, 2024)
Poetry is a form of literature that is appreciated by people of all ages because its messages or meanings are often complex and profound. This article aims to analyze by Chairil Anwar with a semantic approach. This qualitative descriptive research focuses on the lexical, grammatical, referential, and figurative meanings in the poem. Data were collected through literature review. The analysis results show that out of the eight stanzas of the poem, the semantic meaning is dominated by lexical meaning, indicating the use of words with meanings corresponding to the dictionary. Essentially, "Poem Aku" by Chairil Anwar is one of the literary works that depict the poet's subjective feelings and social unrest. In this poem, Chairil Anwar explores themes of self-existence, uncertainty, and rebellion against social norms. Through the use of distinctive and expressive language, he conveys his dissatisfaction and inner turmoil. This poem also reflects the spirit of renewal in Indonesian literature at that time.